Reliability, validity, and maturation-related differences of frontal and sagittal plane landing kinematic measures during drop jump and tuck jump screening tests in male youth soccer players - Robles-Palazón, F. J.; Ruiz-Pérez, I.; Oliver, J. L.; Ayala, F.; de Baranda, P. S (Physical Therapy in Sport, 2021)
Objectives To determine the inter-rater and intra-rater reliability of frontal and sagittal plane landing kinematic measures during drop jump (DVJ) and tuck jump (TJA) tasks in male youth soccer players, to assess the concurrent validity between DVJ and TJA tests, and to evaluate the ability of both tasks to detect differences between players` stage of maturation.